Pólipos colónicos: Estudio clínico, endoscópico e histológico en el Cusco - Daza Valer, Fredy (2001)
One studies the clinical-pathological characteristics of the colonic polyps in 105 subjected patients to exam colonoscopic in the Service of Gastroenterology of the National Hospital South-this ESSALUD Cusco in the period of April 1997 to March 2000. The age average was of 53.43 years. It was found that the total percentage of polyps was 9.6%. The most frequent age in presentation of colon polyps was in bigger than 50 years. The colon polyps are presented with more frequency in the masculine sex. The polyps are located with more frequency in the rectosmoid area (65.7%). Likewise the frequency of presentation to the colon polyps diminishes in relation to the location distal to the rectum. The polyps found correspond in more percentage to polyps among 0.5- 1 cm of size. (42.9%). The polyps in more frequency have unique presentation. The aspect macroscopic sesil prevails on the aspect pediculado. The polyp adenomatous corresponds to 63.81% of the biopsies, followed by the hyperplasic polyps (29,52%). The tubular adenoma is the most frequent in the histological exam. The grade of light pediculados polyps are more frequent in smaller than 18 years.